SURVEI TINGKAT KEBUGARAN JASMANI DI MASA PANDEMI COVID 19 PADA SISWA KELAS VII SMP NEGERI 1 MOJOWARNO - Yunarta, Arsika; Prasetiyo, Rahayu (JOURNAL RESPECS (Research Physical Education and Sports), 2022)
Physical fitness is a state of physical ability that can adjust the function of the body's organs to certain physical tasks and or environmental conditions so that it can be overcome in an efficient way, without experiencing excessive fatigue and has completely recovered to do the same task the next day. This study was conducted to determine the level of physical fitness of students during the pandemic in grade VII students of SMP Negeri 1 Mojowarno. By doing this research is expected to be a suggestion for students in developing their potential and abilities and can determine or add to the mindset and is expected to be developed further. This type of research is a descriptive study with a quantitative approach and uses a simple random sampling technique in sampling. The sample in this study were 4 class VII SMP Negeri 1 Mojowarno namely class VII A, VII C, VII F and VII I with a total of 131 students. The instrument in this study was the Indonesian Physical Fitness Test (TKJI) for ages 13-15.